Frequency reuse and power control for interference mitigation in femtocell lte-a network / Khalil Ahmed Qasem As'ham - Khalil Ahmed , Qasem As'ham (2017)
Currently, femto cells have become the best solution to further enhance services provided by the LTE cellular network, which offers high capacity and high data-rate. This is done by boosting the coverage area and the data rate at restricted areas. The combinations of LTE networks and femto-cells results to a heterogeneous environment, in which a two tier networks that try to fully utilize all the available spectrum. This, however introduces interference. One of the most common solution is investigating the locations of the newly installed femto base station (FBS) and use power control in order to avoid suffering from performance degradation caused by interference. Besides, it is also possible to deploy Inter-cell Interference Cancellation (ICIC) at the macro-cell, which utilizes the spectrum completely or partially to prevent co-channel interference. With the use of Matlab simulation, which is highly configurable, this report will study the interference mitigation techniques under various topologies. In details, the cellular networks have been analyzed and evaluated, as well as the cross-tier interference issues. Also, each interference mitigation technique is deployed and evaluated for various femto-cells. Lastly, the results that got from each method are compared in terms of overall throughput, spectral efficiency and cell-edge users’ performance.